Effect of Leverage, Profitability, Audit Opinion, and Firm Size on Audit Report Lag: Empirical Evidence from Property and Real Estate Sector Companies - Wijaya, Agung Shilvya; Wiralestari, Wiralestari; Safelia, Nela (PT. Riset Press International, 2025)
This study aims to examine the effect of leverage, profitability, audit opinion, and firm size on audit report lag in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. Audit report lag refers to the time gap between the fiscal year-end and the issuance of the independent auditor’s report, which serves as a critical indicator of the timeliness and quality of financial reporting. The research adopts a quantitative approach using multiple linear regression analysis. The sample was determined through purposive sampling, consisting of 29 companies observed over four years, resulting in 116 firm-year observations. The study employed secondary data obtained from officially published annual reports and financial statements. The findings indicate that leverage, profitability, audit opinion, and firm size jointly have a significant effect on audit report lag. In contrast, profitability and audit opinion show a negative and significant effect when tested individually, suggesting that firms with higher profitability and unqualified audit opinions tend to complete audits more quickly. Meanwhile, leverage and firm size do not exhibit a significant impact. These results provide deeper insights into the determinants of audit delay and offer practical implications for enhancing the timeliness of financial reporting in Indonesia’s property sector.